The case for the Enlightenment Scotland and Naples, 1680-1760 - Robertson, John 1951- (Ideas in context, 2005)
The Case for the Enlightenment is a comparative study of the emergence of Enlightenment in Scotland and in Naples. Challenging the tendency to fragment the Enlightenment in eighteenth-century Europe into multiple Enlightenments, the distinguished intellectual historian John Robertson demonstrates the extent to which thinkers in two societies at the opposite ends of Europe shared common intellectual preoccupations. Before 1700, Scotland and Naples faced a bleak future as backward, provincial kingdoms in a Europe of aggressive commercial states. Yet by 1760, Scottish and Neapolitan thinkers were in the van of those advocating the cause of Enlightenment by means of political economy. By studying the social and institutional contexts of intellectual life in the two countries, and the currents of thought promoted within them, The Case for the Enlightenment explains this transformation. John Robertson pays particular attention to the greatest thinkers in each country, David Hume and Giambattista Vico